Production–Living–Ecological Risk Assessment and Corresponding Strategies in China’s Provinces under Climate Change Scenario - Wenjuan Hou; Shaohong Wu; Linsheng Yang; Yunhe Yin; Jiangbo Gao; Haoyu Deng; Maowei Wu; Xiaojie Li; Lulu Liu (Land, 2022)
In the context of the increasing frequency of natural disasters caused by climate change in recent years, rational territorial spatial planning must pay attention to production–living–ecological (PLE) risks under climate change scenarios. In this study, a method synthesizing the Box–Cox transformation and area weighted averaging is established for characterizing the PLE risks in China’s provinces, which are divided into three zones to cope with PLE risks. Further, targeted strategies from the perspective of the disaster-induced factors and disaster-affected objects are explored for the regions within the different zones. The results show that the regions with a high production risk are mainly distributed in Guangdong, Henan, and Shandong, with an index between 0.80 and 1.00; the regions with a high living risk are concentrated in Jiangsu, Anhui, Guangdong, and Hainan, with an index exceeding 0.72; and the regions with a high ecological risk are concentrated in Guangxi, Ningxia, and Yunnan, with an index exceeding 0.50. The overall PLE risk is high along the southeastern coast, intermediate in central and western China, and low on the Tibetan Plateau. From the A to C zones, the number of risk types and intensity of risks requiring attention gradually decrease. For the category A zone, recommended measures include the construction of disaster risk monitoring and early warning systems for coastal cities and major grain-producing regions, the development of urban ecological protection zones, and the adjustment of economic and energy structures, etc. Production and living risks are central to the category B zone, while ecological and production risks are central to the category C zone. This study can provide theoretical support for China’s scientific development of land planning and the realization of a beautiful China.